Characterization of material behaviour under pure shear condition - Hußnätter, Wolfgang; Merklein, Marion (Proceedings of ESAFORM 2008, 2008)
In the last decades the design of sheet metal manufacturing processes and products has been mainly influenced by modern tools, e. g. the large field of numerical simulations based on the finite element (FE-) method. Since the modeling of the material behavior is essential for the quality of the calculated results both the determination of characteristic material data and the transformation of these into material models are of high relevance for the whole process-chain. New materials, e. g. light weight sheet metals often show anisotropic and sometimes also some special forming behavior like the twinning effect of magnesium alloys. Furthermore, car body components become more and more complex concerning the geometry and that leads to a mixture of different stress conditions during forming, e. g. deep drawing, stretching and shearing. As a consequence of these reasons also the material models have to be enhanced and therefore especially the yield locus diagram and the real stress-strain curve must include the relevant material characteristics and data. Nevertheless, the forming behavior of sheet metal under pure shearing condition is not sufficient described. In 1984 Miyauchi proposed a new kind of shear test that is characterized by a symmetrical loading of the specimen and homogenous areas of shearing. In this paper a new tool and a new specimen's geometry are introduced with which shear tests have been done in the style of Miyauchi for different materials. The forming behavior is analyzed using an optical strain measurement system, in order to obtain detailed information on the onset of plastification as well as the homogeneity of the plastification itself. It can be shown that the two shear zones are constant and homogenous during the forming process. Basing on the experimental investigations the real stress-strain curves and the yield loci under pure shear conditions are obtained. © Springer/ESAFORM 2008.
LFT Import::2019-08-05 (1511)
Keywords: Anisotropy; Material characterization; Shear Test; Yield Loci; Yielding